Implementasi Strategi Dalam Penanganan Pembiayaan Macet di BMT UGT Sidogiri Tanggulangin - Mustika Nur Alam (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine the implementation of strategies in handling bad financing at BMT UGT Sidogiri Tanggulangin due to a decrease in the nominal amount deposited by members due to the economic crisis during the Covid-19 pandemic, to deal with these problems, BMT UGT Sidogiri has a good strategy. The research results show that the strategies that have been used by BMT UGT Sidogiri Tanggulangin to deal with non-performing financing are proven to be able to overcome the problems that occur and have a good impact on customer responsibilities and obligations. This study uses qualitative research methods in order to clearly address the problems that occur and the strategies implemented by BMT UGT Sidogiri. Keywords: Bad Financing, BMT Ugt Sidogiri